Menggagas Pendidikan Humanis Religius: Belajar dari Model Pendidikan Pesantren - Mighfar, Shokhibul (Program Pascasarjana Universitas Ibrahimy, 2018)
Indonesian nation experienced a very complex problem. It realized that the powerlessness of education has potential to create a problem that is simple. Education has a very strategic role as a means of human resources and human investment. In the concept of humanist religious education, religion can’t be separated and become a unity of integrity. The Qur'an used four terms to refer to humans, namely are; Bashar, Al-nas, Bani adam, and Al-insan. In the practical level, humanistic religious education has three main objectives that are; quality of culture, autonomous and critical thinking, and authentic personality and has 5 strategies in implementation: there are a balanced combination between approach and objectives, a balance between orientation and information, educational climate or supportive academic culture, a conspicuous and characteristic curriculum, and a good relationship and communication in education.